FURTHER INSIGHTS INTO PALEOINDIAN USE OF THE POWARS II RED OCHER QUARRY (48PL330), WYOMING. Issue 3 (19th April 2018) - Frison, George C.; Zeimens, George M.; Pelton, Spencer R.; Walker, Danny N.; Stanford, Dennis J.; Kornfeld, Marcel
Abstract : We report major new insights from recent research at the Powars II Paleoindian red ocher quarry (48PL330). We salvaged more than 7, 000 artifacts from Powars II between 2014 and 2016 by screening redeposited sediment from the talus slope below the intact portion of the site. Clovis artifacts dominate the diagnostic artifact assemblage, including 53 Clovis points, 33 preforms, and artifacts associated with a previously unrecognized blade core industry. We report the first radiocarbon dates from the site, determined from dating bone tools, which indicate Cody-aged use (ca. >10, 000 cal BP). Further, salvage efforts discovered a previously unknown toolstone source from which many of the Clovis artifacts were produced. The Powars II Clovis points most resemble early Paleoindian points from the far Northern Plains and were likely both produced and discarded in the red ocher quarry after hunting, as evidenced by preform production and the presence of impact fractures on many used points. Given these production and discard patterns, Powars II holds some of the best evidence archaeologists currently have for Paleoindian ritualism related to hunting. Abstract : Presentamos nuevas perspectivas importantes derivadas de investigaciones recientes en la cantera de ocre rojo Paleoindia Powars II (48PL330), ubicada en la parte oriental del estado de Wyoming. Recuperamos más de 7, 000 artefactos en Powars II entre 2014 y 2016 mediante el tamizado de sedimentos redepositados en el talud abajo de la parte intacta del sitio. Los artefactos Clovis predominan en el ensamblaje de artefactos diagnósticos, incluyendo 53 puntas Clovis, 33 preformas y artefactos asociados con una industria de núcleo de hojas no identificada previamente. Presentamos las primeras fechas de radiocarbono procedentes del sitio, determinadas a través del fechado de herramientas de hueso, que indican uso durante el complejo Cody (ca. 10.000 cal aP). Además, las investigaciones descubrieron una cantera previamente desconocida de la cual se extrajo el material para producir muchos de los artefactos Clovis. Las puntas Clovis de Powars II tienen el mayor parecido con las primeras puntas Paleoindias del extremo norte de las Planicies norteamericanas y probablemente fueron producidas y desechadas en la cantera de ocre rojo después de cazar, como lo demuestra la producción de preformas y la presencia de fracturas por impacto en muchas puntas. Powars II proporciona algunas de las mejores evidencias encontradas hasta la fecha para el ritualismo Paleoindio relacionado con la caza.